The limitations of artificial intelligence (legal problems) - Alexander E. Evstratov; Igor Yu. Guchenkov (Правоприменение, 2020)
The subject. Possible problems that may lead to further use of artificial intelligence, as well as ways to overcome them are studied.The purpose of the article is to identify the principles of the legal status of artificial intelligence.The methodology includes formal-logical method, systematic approach, formal-legal method, comparative method, analysis, synthesis.The main results of the research. The basic approaches to the definition of the concept of artificial intelligence are examined, specific examples are given, the problems that can cause the further use of artificial intelligence are analyzed. Artificial intelligence as a complex computing system is characterized by: variability in decision-making, a certain degree of autonomy when working, as well as the ability to take into account the experience gained from previously made decisions and use it to correct them. The challenges that are facing both the legislators and scientists are identified, such as: determining the status of artificial intelligence, responsibility for its actions and, accordingly, finding the most acceptable way to transform legislation governing the use of artificial intelligence.Conclusions. Artificial intelligence, due to both its novelty and certain functioning features, causes disagreement in the scientific community regarding the permissible limits of its application, its legal status, responsibility for the results of its activities, as well as on many other related issues. Today there is no unity of opinion even in relation to the definition of the term “artificial intelligence”, which is largely due to the previously mentioned features. Therefore, in a world of continuous scientific and technological progress, where artificial intelligence plays an increasing role, we should continue to study these technologies in order to: firstly, determine their role and place in the future of humanity; secondly, to define the permissible limits of the use of artificial intelligence in order not to harm individual people or groups of people; thirdly, based on an understanding of the nature and principles of artificial intelligence, transform legislation in such a way that it best meets the challenges, which legal scholars will have to face in the future.